The Role of Acute Trigemino-Cardiac Reflex in Unusual, Non-Surgical Cases: A Review - Chowdhury, Tumul; Schaller, Bernhard (Frontiers in Neurology, 2016)
Trigemino-cardiac reflex is a well established phenomenon that is mainly reported in the various surgical specialities. However, the role of this unique reflex is entirely unknown in other medicine domains. Therefore, the present mini-review aims to explore the role of TCR in such unusual cases and also highlights the importance of case reports for knowledge creation in such context.